Concepções de professores atuantes e em formação sobre a história da química e a natureza da ciência - Santos, Anderson de Oliveira (2016)
Discussions on the importance of the use of the history of science in the process of teaching and learning of disciplines such as: Chemistry, physics and biology, both in high school and in teacher training, be it initial or continued, have been increasingly applicants. Among the contributions to the use of the history of science in science education include collaboration in the process of teaching and learning in science concept learning or understanding of the very nature of Science, that is, how scientific knowledge is constructed and how the thinking and "do" Science and scientists. This study aimed to investigate the conceptions of licenciandos about the history of chemistry and its use in teaching, as well as in their views about the nature of science. For validation of our data collection instruments, we use Active Chemistry teachers. As a reference used analysis of Textual analysis of Discursive Moraes and Galiazzi (2011). The results of this study showed some distorted views on the history of chemistry and the nature of science, for example, the mere citation of dates and historical events of science.